The Influence of Experiential Marketing and Store Atmosphere on Repurchase Intention through Consumer Satisfaction at Tyga Per Ampat Cafe - Muryati, Elsa; Sukardi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
The coffee industry in Pontianak has deep cultural roots, with coffee consumption being a common social activity across all ages. One key player in this sector is Tyga Per Ampat Cafe. This study examines the impact of Experiential Marketing and Store Atmosphere on Repurchase Intention at Tyga Per Ampat Cafe, with Consumer Satisfaction as an intervening variable. Using an associative method, the research surveyed 100 customers who had previously visited the cafe. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS 3.0 software. The results show that Experiential Marketing does not directly impact Consumer Satisfaction but directly influences Repurchase Intention. Store Atmosphere positively affects Consumer Satisfaction but does not impact Repurchase Intention. Consumer Satisfaction, however, has a direct positive effect on Repurchase Intention. Additionally, Consumer Satisfaction does not mediate the effect of Experiential Marketing on Repurchase Intention but does mediate the impact of Store Atmosphere on Repurchase Intention.